RISK OF THROMBOEMBOLIC COMPLICATIONS AND ANTITHROMBOTIC THERAPY IN IN-PATIENTS WITH PERMANENT AND RECURRENT ATRIAL FIBRILLATION IN REAL CLINICAL PRACTICE - I. V. Grajfer; L. E. Kuvshinova; P. V. Dolotovskaya; O. V. Reshet'ko; N. V. Furman (Столичная издательская компания, 2015)
Aim. Тo evaluate compliance of ongoing antithrombotic therapy (ATT) in various forms of atrial fibrillation (AF) with the risk level of thromboembolic complications (TEC), calculated with the СHADS2 and CHA2DS2-VASc scales in real clinical practice. Material and methods. A retrospective study of hospital records of 308 in-patients admitted to the cardiology departments of two multidisciplinary hospitals during the year because of nonvalvular AF . Risk of thromboembolic complications was estimated with the CHADS2 and CHA2DS2-VASc scales and appointed ATT was analyzed. Results. Patients with high risk of TEC were predominated in the study population: 77.6% and 91.9% according to CHADS2 and CHA2DS2-VASc scales, respectively. Moderate risk was found in  17.6%  and  6.1%  of  patients  according  to  CHADS2 and  CHA2DS2-VASc  scales,  respectively.  Only  32.2%  and  28.6%  28.6%  of  patients  at  high  risk  according  to  CHADS2 and  CHA2DS2-VASc scales, respectively received warfarin in hospital. All patients with permanent AF in this sample had a high risk of TEC according to the both scales. In the group of paroxysmal/persistent AF the high, moderate and low risk of TEC was identified in 87%, 9.9%, and 3.1% of patients, respectively , according to CHA2DS2-VASc scale and in 64.25%, 28.5% and 7.5% of patients, respectively , according to CHADS2 scale. Difference in high-risk patient rate was not significant among patients with permanent AF . In high risk group contraindications for receiving indirect anticoagulants were more frequent in the group with permanent AF (OR 3.1; 95% CI 0.88-10.7; p>0,05). The probability of warfarin prescription in patients with permanent AF was higher than in patients with paroxysmal or persistent AF (OR 1.98, 95% CI 1,18-3,31), and probability of aspirin prescription was lower (OR 0.82; 95% CI 0,51-1,32; p>0,05).  Conclusion. In real clinical practice oral anticoagulants are prescribed insufficiently in patients at high risk. Usage of CHA2DS2-VASc scale compared with usage of CHADS2 scale, leads to significant increase in the proportion of patients at high risk due to reduction in the proportion of patients with moderate risk in persistent or permanent AF . Usage of CHADS2 scale can lead to an underestimation of the TEC risk in patients with persistent or permanent AF .